2022
DOI: 10.3389/fphar.2022.1009705
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and molecular analysis of the effects of Huangqi Jianzhong decoction on proliferation and apoptosis in GES-1 cells infected with H. pylori

Abstract: Background: Infection with Helicobacter pylori (H. pylori) can cause chronic gastritis and other digestive tract diseases, and represents a public health concern. Current anti-H. pylori treatment can result in antibiotic resistance and other adverse reactions. Huangqi Jianzhong decoction (HQJZD) is a prescription form of traditional Chinese medicine for chronic gastritis that increases probiotics and inhibits H. pylori. In this study, its anti-bacterial activity against H. pylori receives a preliminary evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It has been shown that some TCM compounds, such as Banxia Xiexin Decoction [ 17 ], Huangqi Jianzhong Tang [ 18 , 28 ], and Sijunzi decoction [ 21 ], are effective in inhibiting H. pylori according to clinical studies in the previous article. In addition, Jinghua Weikang capsule, a modern TCM (approved No.…”
Section: Pharmacological Mechanisms Of Tcm For the Treatment Of Cgmentioning
confidence: 99%
“…It has been shown that some TCM compounds, such as Banxia Xiexin Decoction [ 17 ], Huangqi Jianzhong Tang [ 18 , 28 ], and Sijunzi decoction [ 21 ], are effective in inhibiting H. pylori according to clinical studies in the previous article. In addition, Jinghua Weikang capsule, a modern TCM (approved No.…”
Section: Pharmacological Mechanisms Of Tcm For the Treatment Of Cgmentioning
confidence: 99%
“…The main mechanisms of action of TCM include suppressing the replication and transcription of H. pylori , reducing urease expression, destroying the bacterial structure, downregulating the expression of virulence factors, and inhibiting the activation of signaling proteins ( Li et al., 2018 ; Xu et al., 2021 ; Yang et al., 2021 ). Several TCM prescriptions, including Shen-ling-bai-zhu-san and Huangqi Jianzhong decoction, have also shown the capability to treat H. pylori infections ( Hu et al., 2022 ; Jin et al., 2022 ). Integration of the aforementioned TCM herbs and their active constituents with conventional experiential therapy has the potential to yield substantial augmentation in the eradication rate of H. pylori and the clinical efficacy in managing diverse gastrointestinal disorders associated with the bacterium.…”
Section: Treatmentmentioning
confidence: 99%
“…Nevertheless, conventional cell lines can still be considered a convenient system for applications such as screening of compounds with potential therapeutic activity and proof of concept validation of pathogenetic mechanisms. In this regard, GES-1 cells have been used by several groups, including ours, to test potential anti-gastritis agents (see for example references [11][12][13][14]). Furthermore, the effects of H. pylori on genomic instability and expression of oncogenes have been investigated in GES-1 cells [15,16]; nevertheless, an in-depth characterization of the pathways triggered in this cell line in response to inflammatory stimuli and pathogens is still incomplete.…”
Section: Introductionmentioning
confidence: 99%